2020
DOI: 10.1186/s12883-020-01749-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis in a multi-ethnic population from Northern California: a retrospective analysis, 2010–2016

Abstract: Background: Research is needed to examine differences in multiple sclerosis (MS) prevalence by race-ethnicity. The goal of this study was to quantify MS prevalence in a health care system in Northern California and examine differences in prevalence and phenotype by race-ethnicity. Methods: We conducted a retrospective, observational cohort study of adults (2010-2016). MS prevalence estimates were standardised to distributions of gender and race-ethnicity for the underlying geographic region and stratified by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…We found that Non-AJ MS patients differed from their Ashkenazi counterparts in several demographic characteristics. The ratio between females and males in the AJ group was 2.7:1, similar to reports in European countries 30 , 31 , while Non-AJ patients had a ratio of 1.6:1, smaller than that of any ethnic population recently studied 32 . Non-Ashkenazi patients in our sample were younger at the time of EDSS evaluation and at disease onset compared to Ashkenazi patients, these differences in age remained consistent when analyzing Israeli natives separately and thus cannot be attributed to immigration effect.…”
Section: Discussionsupporting
confidence: 87%
“…We found that Non-AJ MS patients differed from their Ashkenazi counterparts in several demographic characteristics. The ratio between females and males in the AJ group was 2.7:1, similar to reports in European countries 30 , 31 , while Non-AJ patients had a ratio of 1.6:1, smaller than that of any ethnic population recently studied 32 . Non-Ashkenazi patients in our sample were younger at the time of EDSS evaluation and at disease onset compared to Ashkenazi patients, these differences in age remained consistent when analyzing Israeli natives separately and thus cannot be attributed to immigration effect.…”
Section: Discussionsupporting
confidence: 87%
“… 27 BIPOC patients also face worse MS outcomes, and potentially even increasing incidence. 28 , 29 As sharply illustrated when examining disparities in clinical outcomes related to the COVID-19 pandemic in the general population, these disparities are linked to differences in access, SES and discrimination. Outside of the United States as well, studies have linked low SES and minority racial group status with increased risk of MS-related disability.…”
Section: Discussionmentioning
confidence: 99%
“…First among the reasons for enrollment targets, there is evidence that MS may differ in both risk factors and disease severity in certain racial and ethnic groups. People who identify as African American, LatinX, Middle Eastern, and North African are reported to have increased disease activity, more lasting disability, and/or worse clinical outcomes (8)(9)(10)(11)(12)(13). Other characteristics relevant to MS including early life exposures or vitamin D levels may differ (14).…”
Section: For Againstmentioning
confidence: 99%